Implementação de modelo computacional empregando ferramenta de CFD para análise do comportamento hidráulico de bomba carneiro não industrial - Logatti, Bruna (Universidade Federal de São Carlos, 2024)
In urban settlements or rural areas households are often located near regions with abundant water availability. However, in many cases, there is a lack of financial resources for the acquisition and implementation of basic electrical infrastructure for conventional water supply solutions. Hydraulic rams or ram pumps are devices used to elevate water, and they operate using only hydraulic energy. These devices can be seen as a sustainable alternative for water transportation. However, when analyzing the current scientific production on the subject, many obstacles are encountered. The scientific output is limited to this day, and there is also a noticeable absence of studies focused on agronomy and agriculture, the development of low-cost hydraulic ram models, the use of new technologies for modeling, and the optimization of the ram pump model. In this context, computational fluid dynamics, also known as CFD, can be seen as a solution. This study aims to apply CFD techniques in the internal flow modeling of a non-industrial ram pump. The 3D model of the ram pump was constructed using Blender software, based on the study by Oliveira Junior et al (2021). Initially, it was decided to use OpenFOAM software for the simulations; however, due to difficulties encountered in adapting the mesh to the program, it was changed to Ansys Discovery 2023 software. Four different meshes were developed, four scenarios were created for the simulation, varying the volume of the air chamber, each of them containing seven simulations, varying the pressure loads. Results unveiled fundamental operational principles of the hydraulic ram, including the influence of pressure load at the pump inlet on inlet flow, the relationship between pressure loads at the outlet and inlet, and the significance of air chamber size in water displacement.
Implementation of computational model employing CFD Tool to analyze the hydraulic behavior of a non-industrial ram pump
Keywords: Carneiro hidráulico; CFD; Ansys Discovery 2023; Modelagem computacional; Abastecimento de água; Hydraulic ram; Computational modeling; Water supply; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDRAULICA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS::ENGENHARIA SANITARIA; ENGENHARIAS